The wall-flow-guided and interferential interactions of the lateral swirl combustion system for improving the fuel/air mixing and combustion performance in DI diesel engines. (1st January 2019) - Chen, Yanlin; Li, Xiangrong; Li, Xiaolun; Zhao, Weihua; Liu, Fushui
Abstract: The lateral swirl combustion system was designed based on and to improve upon the traditional ω-type combustion system. Previous research has verified the outstanding combustion performance of the lateral swirl combustion system. In this study, to reveal the interaction mechanisms between the lateral swirl combustion chamber and spray jets, experimental and numerical study was conducted at various spray incident angles ( φ ) where the relations between the combustion chamber and spray jets are different. The spray impinging processes and combustion performance were measured in a single-cylinder diesel engine with an endoscopic system. The distribution of velocity and the equivalence ratio was analyzed through simulation. Then, under the optimal φ, the fuel/air mixing quality and combustion performance was verified in comparison with a double swirl combustion system. The results show that fuel consumption and soot emissions of the lateral swirl combustion system decreased with an increasing spray incident angle. When φ reached its maximum, the combustion system exerted the best combustion performance, because the wall-flow-guided interaction between the chamber and spray jets and the interferential interaction from the neighboring wall jets were optimized. This combined effect promoted in-cylinder fuel/air mixing and combustion. Under this circumstance, the indicated thermal efficiency of the lateral swirl combustion system increased by 3.4–6.8% compared with the double swirl combustion system, and the soot emissions decreased in the ranges of 45–73%. It was concluded that the lateral swirl combustion system with a maximum spray incident angle significantly improves the combustion performance of DI diesel engines due to the wall-flow-guided and interferential interactions between the combustion chamber and spray jets. These findings are key to the design and development of a high-efficiency lateral swirl combustion system for DI diesel engines. Highlights: The effect of the spray incident angle on combustion characteristics was studied. The visual spray impinging process in a DI diesel engine was analyzed. The wall-flow-guided and interferential interactions of the combustion system were revealed. The combustion performance improves significantly under a maximum spray incident angle.